On the connection between normative reasons and the possibility of acting for those reasons - Sinclair, Neil (Springer, 2016)
According to Bernard Williams, if it is true that A has a normative reason to Φ then it must be possible that A should Φ for that reason. This claim is important both because it restricts the range of reasons which agents can have and because it has been used as a premise in an argument for so-called ‘internalist’ theories of reasons. In this paper I rebut an apparent counterexamples to Williams’ claim: Schroeder’s (2007) example of Nate. I argue that this counterexample fails since it underestimates the range of cases where agents can act for their normative reasons. Moreover, I argue that a key motivation behind Williams’ claim is compatible with this ‘expansive’ account of what it is to act for a normative reason.